Long-term tea consumption reduces the risk of frailty in older Chinese people: Result from a 6-year longitudinal study - Gao, Tianjing; Han, Siyue; Mo, Guangju; Sun, Qing; Zhang, Min; Liu, Huaqing (Frontiers in Nutrition, 2022)
Background: Vast accumulative evidence suggests that the consumption of tea and its components have various potential health benefits. This study used a longitudinal study to examine the causality between tea consumption and frailty in older Chinese people. Methods: This study employed the longitudinal data from 2008 to 2014 of the Chinese Longitudinal Healthy Longevity Survey (CLHLS), which were systematically collected through face-to-face interviews. 2473 participants completed six-follow-up surveys in 2014 and were analyzed in this study. The frailty index recommended by Searle and co-authors, including 44 health deficits, was used. A Generalized Estimating Equation (GEE) was applied to determine the risk ratio (RR) with a 95% confidence interval (CI) for frailty, and further subgroup analyses were conducted to investigate whether the risk differed stratified by age, sex, and socioeconomic status. Additionally, the interaction between tea consumption with sex and frailty was tested. Results: Of the 2473 participants, 14.1% were consistent daily tea drinkers, and 22.6% reported frailty at the 6-year follow-up. Compared to non-tea drinkers, consistent daily tea drinkers reported a significantly lower ratio of having frailty (risk ratio [RR] = 0.54, 95% confidence interval [CI]: 0.38–0.78), adjusting for sociodemographic characteristics, health behavior, socioeconomic status, and chronic illnesses. In further subgroup analyses, consistent daily tea consumption significantly reduced the risk of frailty for males (RR = 0.53, 95% CI: 0.32–0.87) but not females (RR = 0.65, 95% CI: 0.37–1.12); in the young (RR = 0.40, 95% CI: 0.22–0.74) but not in the oldest (aged ≥ 80) (RR = 0.66, 95% CI: 0.40–1.06); informal education (RR = 0.48, 95% CI: 0.28–0.84) but not formal education (RR = 0.62, 95% CI: 0.37–1.03); financial dependence (RR=0.42, 95% CI:0.25 - 0.71) but not financial independence (RR = 0.71, 95% CI: 0.41–1.23). Additionally, females showed a lower tea-mediated risk of frailty in occasional tea consumers (RR = 0.51, 95% CI: 0.29–0.89) and inconsistent tea drinkers (RR = 0.58, 95% CI: 0.37–0.93). Conclusions: Habitual tea consumption can reduce the risk of frailty in older Chinese, and the benefit varied by age, sex, education, and financial support.